Synergistic Cu/Pd‐Catalyzed Asymmetric Allenylic Alkylation of Azomethine Ylides for the Construction of α‐Allene‐Substituted Nonproteinogenic α‐Amino Acids - Liu, Hua‐Chao; Hu, Yuan‐Zheng; Wang, Zuo‐Fei; Tao, Hai‐Yan; Wang, Chun‐Jiang (Chemistry : a European journal, 2019)
An unprecedented asymmetric allenylic alkylation of readily available imine esters, which was enabled by a synergistic Cu/Pd catalysis, has been developed. This dual catalytic system possesses good substrate compatibility, delivering a diverse array of nonproteinogenic α‐allenylic α‐mono‐ or α,α‐disubstituted α‐amino acids (α‐AAs) with high yields and generally excellent enantioselectivities. Furthermore, the scalability and practicability of the current synthetic protocol were proven by performing gram‐scale reactions and by the first catalytic asymmetric synthesis of naturally occurring (S)‐γ‐allenic α‐amino acid, respectively. Synergy for asymmetry: An unprecedented asymmetric allenylic alkylation of readily available imine esters enabled by a synergistic Cu/Pd catalysis has been developed. This dual catalytic system possesses good substrate compatibility, delivering a diverse array of nonproteinogenic α‐allenylic α‐mono‐ or α,α‐disubstituted α‐amino acids with high yields and generally excellent enantioselectivities. Gram‐scale reactions were performed, and the synthetic protocol allowed for the first catalytic asymmetric synthesis of naturally occurring (S)‐γ‐allenic α‐amino acids.